Strategi Brand Image Wisata Dalam Meningkatkan Minat Calon Peserta Didik Baru di MAN Sampang - Badruttamam Badruttamam; Fathorrahman Z; Aji Sohib (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2022)
In the current era of globalization, in the world of education there is competition between one institution and another. Then the tourism brand image strategy in increasing the interest of prospective new students at MAN Sampang. Based on this, there are three research focuses that are the main studies in this study, namely: first, how to plan a tourism brand image strategy in increasing the interest of prospective new students at MAN Sampang?, second, how to implement a tourism brand image strategy in increasing interest prospective new students at MAN Sampang?, third, how to evaluate the tourism brand image strategy in increasing the interest of prospective new students at MAN Sampang?. This research method uses a descriptive qualitative approach. The sources of data obtained are through interviews, observation and documentation. The informants were the principal of the MAN Sampang school, the waka and all members of the MAN Sampang school. The results showed that: first, planning the tourism brand image strategy in increasing the interest of prospective new students at MAN Sampang, is to hold a meeting of the principal with the entire board of teachers and TU staff to discuss and determine the brand image that is in accordance with MAN Sampang and preparing a work program and creating a committee to build a tourism brand at MAN Sampang. Second, in implementing the tourism brand image strategy at MAN Sampang, it is to build and rearrange the school environment and provide photo spots as a forum for expression for madrasa residents. The third evaluation of the tourism brand image strategy at MAN Sampang is that the principal often holds meetings with the committee and the entire teacher council so that later it can be easier to develop the tourism brand image that has been carried out at MAN Sampang.